Implementation of fragile X syndrome carrier screening during prenatal diagnosis: A pilot study at a single center - Xi, Hui; Xie, Wanqin; Chen, Jing; Tang, Wanglan; Deng, Xiuli; Li, Hua; Peng, Ying; Wang, Dan; Yang, Shuting; Zhang, Yanan; Duan, Ranhui; Fang, Junqun; et al. (Molecular genetics & genomic medicine, 2021)
Background Fragile X syndrome (FXS) is the most common inherited form of intellectual disability. Prenatal screening of FXS allows for early identification and intervention. The present study explored the feasibility of FXS carrier screening during prenatal diagnosis for those who were not offered screening early in pregnancy or prior to conception. Methods Pregnant women to be offered amniotic fluid testing were recruited for the free voluntary carrier screening at a single center between August, 2017 and September, 2019. The number of CGG repeats in the 5’ un‐translated region of the fragile X mental retardation gene 1 (FMR1) was determined. Results 4286 of 7000 (61.2%) pregnant women volunteered for the screening. Forty (0.93%), five (0.11%), and three (0.07%) carriers for intermediate mutation (45–54 repeats), premutation (55–200 repeats) and full mutation (>200 repeats) of the FMR1 gene were identified respectively. None of the detected premutation alleles were inherited by the fetuses. Of the three full mutation carrier mothers, all had a family history and one transmitted a full mutation allele to her male fetus. Conclusion Implementation of FXS carrier screening during prenatal diagnosis may be considered for the need to increase screening for FXS. The present study explored the feasibility of FXS carrier screening during prenatal diagnosis for those who were not offered screening early in pregnancy or prior to conception. Implementation of FXS carrier screening during prenatal diagnosis may be considered for the need to increase screening for FXS.